2012
DOI: 10.2147/imcrj.s32217
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic syringoid eccrine carcinoma of the nipple

Abstract: Syringoid eccrine carcinoma is a very rare skin tumor. Herein we describe a 72-year-old male patient presenting with a syringoid eccrine carcinoma of the nipple with associated axillary lymph node metastases. Surgery associated with adjuvant radiotherapy was performed. To the best of our knowledge, this is the first case of syringoid eccrine carcinoma of the nipple ever reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Tumor cells can organize into nests, cords, or tubules, some of which exhibit a morphology resembling tadpole-like syringoma due to the cords of epithelial tissue. Cytonuclear atypia is not very evident, as is the presence of mitotic activity, which may even be absent [1,11,14,16]. The epithelial component of the tumor may show a cribriform pattern in focus (Figure 3), which makes it difficult to distinguish from other tumors [3].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tumor cells can organize into nests, cords, or tubules, some of which exhibit a morphology resembling tadpole-like syringoma due to the cords of epithelial tissue. Cytonuclear atypia is not very evident, as is the presence of mitotic activity, which may even be absent [1,11,14,16]. The epithelial component of the tumor may show a cribriform pattern in focus (Figure 3), which makes it difficult to distinguish from other tumors [3].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in addition to the immunohistochemical pattern disagreeing with the morphological pattern, there is no accumulation of mucin, as occurs in ADC, favoring the diagnosis of SEC [3,14,19,17]. Imaging studies have been reported to be important but for delimiting the lesion, but not for diagnosis of SEC [11], or searching for metastases [9,10,15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,7,8 The tumor is primarily composed of thin strands and nests of cuboidal epithelium with variable degrees of glandular differentiation. 2 Intracytoplasmic lumina are sometimes evident.…”
Section: Discussionmentioning
confidence: 99%
“…Histologically, SEC have a variety of histological feature and show dilated tubules within dense fibrocollagenous matrix, sometimes with a tadpole appearance, small neoplastic ducts, solid islands, cellular cords, and keratinizing and nonkeratinizing cysts 14 . Cells show mild to marked nuclear atypia, usually of moderate atypia and a variable number of mitoses.…”
Section: Discussionmentioning
confidence: 99%